Quadriceps and hamstring muscle activity during cycling as measured with intramuscular electromyography - da Silva, J. C. L.; Tarassova, O.; Ekblom, M. M.; Andersson, E.; Rönquist, G.; Arndt, A. (European Journal of Applied Physiology, 2016)
Purpose: The aim of this study was to describe thigh muscle activation during cycling using intramuscular electromyographic recordings of eight thigh muscles, including the biceps femoris short head (BFS) and the vastus intermedius (Vint). Methods: Nine experienced cyclists performed an incremental test (start at 170 W and increased by 20 W every 2 min) on a bicycle ergometer either for a maximum of 20 min or to fatigue. Intramuscular electromyography (EMG) of eight muscles and kinematic data of the right lower limb were recorded during the last 20 s in the second workload (190 W). EMG data were normalized to the peak activity occurring during this workload. Statistical significance was assumed at p = 0.05. Results: The vastii showed a greater activation during the 1st quadrant compared to other quadrants. The rectus femoris (RF) showed a similar activation, but with two bursts in the 1st and 4th quadrants in three subjects. This behavior may be explained by the bi-articular function during the cycling movement. Both the BFS and Vint were activated longer than, but in synergy with their respective agonistic superficial muscles. Conclusion: Intramuscular EMG was used to verify muscle activation during cycling. The activation pattern of deep muscles (Vint and BFS) could, therefore, be described and compared to that of the more superficial muscles. The complex coordination of quadriceps and hamstring muscles during cycling was described in detail.